О родственных связях между ископаемой бурозубкой из среднеголоценовых отложений р. Десны и рецентной бурозубкой арктической - Межжерин, В.А.; Свистун, В.И. (Вестник зоологии, 1968)
The authors present a comparison of the fossil Sorex araneus from the middle holocene deposits of the Desna river with the recent Sorex articus and also with the fossil forms, similar to the recent one.